2016
DOI: 10.1007/s00270-016-1367-5
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Comparison of Ultrasound-Assisted Catheter-Directed Thrombolysis and Catheter-Directed Thrombolysis Alone for Treatment of Proximal Deep Vein Thrombosis

Abstract: BackgroundRecent studies have suggested that catheter-directed thrombolysis (CDT) reduces development of post-thrombotic syndrome (PTS). Ultrasound-assisted CDT (USCDT) might enhance the efficiency of thrombolysis. We aimed to compare USCDT with CDT on efficacy, safety, development of PTS, and quality of life after long-term follow-up.MethodsWe describe a retrospective case series of 94 consecutive patients admitted with iliofemoral or more proximal deep vein thrombosis (DVT) to the University Hospital from 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 29 publications
1
10
0
1
Order By: Relevance
“…The occurrence of severe post thrombotic syndrome after primary treatment with isolated-pharmaco-mechanical thrombolysis device is low [33]. But others have not confirmed these findings [34]. In a Cochrane review reduced incidence of post-thrombotic syndrome (by 1/3 rd ), similar effectiveness was seen with systemic thrombolytic therapy and catheter directed thrombolysis [35].…”
Section: Management Of Recurrent Vtesupporting
confidence: 48%
“…The occurrence of severe post thrombotic syndrome after primary treatment with isolated-pharmaco-mechanical thrombolysis device is low [33]. But others have not confirmed these findings [34]. In a Cochrane review reduced incidence of post-thrombotic syndrome (by 1/3 rd ), similar effectiveness was seen with systemic thrombolytic therapy and catheter directed thrombolysis [35].…”
Section: Management Of Recurrent Vtesupporting
confidence: 48%
“…CDT was preferred because no intracranial bleeding was reported in the landmark prospective trial (CaVenT) [7] . Moreover, there were no differences in the safety outcomes of major and minor bleeding events between the traditional CDT and the USCDT groups with acute DVT [8] . USCDT has the additional benefits of shorter intervention duration, shorter hospitalization time, and fewer stent implantations.…”
Section: Discussionmentioning
confidence: 86%
“…The most recent studies and large scale trials have used the continuous infusion technique. 4,5,14,16 However, no comparative studies have Figure 1. Cumulative rate of patent deep venous system without reflux (Kaplan-Meier).…”
Section: Discussionmentioning
confidence: 99%
“…Even though the rate of stent insertion was slightly lower than in other studies, the present outcomes are comparable or even better than previously reported. 4,14,16,19,20 Moreover, the high number (79%) of patients with patent deep veins without reflux at 7 years suggests that a sufficient number of stents were inserted. Unfractionated heparin and LMWH was equally effective as a concomitant anticoagulant during CDT (data not shown).…”
Section: Discussionmentioning
confidence: 99%